Does board committee independence affect financial distress likelihood? A comparison of China with the UK - Ashraf, Sumaira (2021)
This study explores the relationship between board committees’ independence and the financial distress of firms in China and the UK. Akin to previous literature, we estimate this relationship between 2007 and 2016 using a conditional logit model on a sample of matched pair firms. For China, the results indicate that there is a positive and statistically significant association between the percentage of independent audit committee members and the financial distress of firms. In Contrast, the opposite relationship was found for independent compensation and nomination committee members. For the UK, the relationships are the same, but the results are significant only for nomination committee independence. Our overall results suggest that independent audit committee members are not favorable for firm survival. In contrast, the independent compensation and nomination committee members are beneficial for the financial health of firms, as they are responsible for designing fair compensation packages and for selecting the most suitable persons to decide the strategic moves of the firm, respectively. A robustness test demonstrates that the results are robust to the assumed functional form imposed by the conditional logit model and confirms our core findings for both Chinese and UK firms.